Character Education: Examining The Thoughts of Sheikh Burhanuddin Az-Zarnuji and Kh. Imam Zarkasyi - Nuriz, M. Adib Fuadi (Tun Dr. Mahathir Mohamad Thoughts Institute (IPDM), 2018)
The world of education at the present time is considered incapable of building the personality and character of students well, especially with the prevalent modern problems such as student crime and violence, as well as their involvement in drugs and free sex. Therefore, character education is now becoming a contemporary important issue and discussed by many scholars everywhere. One of the interesting relevant studies is the concept of character education as well as its models and patterns of applicability in educational institutions. This study examines the thoughts of two prominent Islamic educationists, Burhanuddin Az-Zarnuji and KH. Imam Zarkasyi, on character education. Both of these figures have established the foundations of character education and became as main references for researchers of Islamic education. This study is a qualitative study using library research methods, and critical analysis. Researchers also conduct field observations to establish the data and reality directly. From the findings of the study, it is evident that Az-Zarnuji and KH. Imam Zarkasyi share a common concept of character education: both agree that education is not only to transfer knowledge or intellectual transfer but also of transferring values and skills. KH. Imam Zarkasyi did not simply take the concept of Islamic education from Az-Zarnuji, but he had successfully implemented the concept directly in the education pattern of Pondok Modern Darussalam Gontor, from 1926 to 1985. KH. Imam Zarkasyi also succeeded in realizing the integration of the soul, values, systems and operational standards in managing the implementation of character education at the school. With totality management, the process of character education was considered fully successful.